Hasil Rapat Konsultasi Bidang Pembinaan Operasional Program Keluarga Berencana Nasional (Badan Koordinasi Keluarga Berencana Nasional, 1984)
Proceedings of an advisory meeting on the development of family planning operational programs in Indonesia.